A Plural Self for a Referential Universe. Self-Reflection, Authorial Image and Borgesian Transreferentiality in Two Songs by Javier Krahe (Anclajes, 2026)
Spanish singer-songwriter Javier Krahe (1944-2015) repeatedly acknowledged Jorge Luis Borges (1899-1986) as one of his main influences. Along with the other two authors of his “three Bs,” Georges Brassens (1921-1981) and Luis Buñuel (1900-1983), he adopted and adapted many of their characteristic discursive mechanisms in his own work. In two particularly remarkable songs, the author not only makes this influence explicit, but also thematizes it: “...Y todo es vanidad” (Corral de cuernos, 1985) and “Matilde Urbach” (Querencias y extravíos, 2007). The first is a self-reflexive song in which the reference to Borges allows Krahe to extend the authorial reflection to the metadiscursive; the second is a tribute built on a transreferential display that recovers, reworks, and reinterprets the Argentine's work. To approach this study, we examine the relationship between the typology of transreferentiality and autopoetic and authorial studies, within the general framework of musical-literary relationships.
Keywords: Javier Krahe; Jorge Luis Borges; Song; Poetry; Literary analysis